2018
DOI: 10.1515/humo-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of static and dynamic measures of lower limb joint angles in cycling: application to bicycle fitting

Abstract: Purpose. Configuration of bicycle components to the cyclist (bicycle fitting) commonly uses static poses of the cyclist on the bicycle at the 6 o'clock crank position to represent dynamic cycling positions. However, the validity of this approach and the potential use of the different crank position (e.g. 3 o'clock) have not been fully explored. Therefore, this study compared lower limb joint angles of cyclists in static poses (3 and 6 o'clock) compared to dynamic cycling. Methods. Using a digital camera, right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…We found a significant difference of around 8°b etween static and dynamic KA with pedal at BDC for the total population. This result is in the range with those reported in previous studies [6], [8], [11], [22], i.e., between 5 to 10°. Therefore, we can suggest a new range of 33-43° for KA during Dynamic BDC by adding 8° to the optimal range of 25-35° without pedalling [16].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found a significant difference of around 8°b etween static and dynamic KA with pedal at BDC for the total population. This result is in the range with those reported in previous studies [6], [8], [11], [22], i.e., between 5 to 10°. Therefore, we can suggest a new range of 33-43° for KA during Dynamic BDC by adding 8° to the optimal range of 25-35° without pedalling [16].…”
Section: Discussionsupporting
confidence: 90%
“…The alterations of KA between static and dynamic conditions would be related to the larger HA and the smaller AA during pedalling. Thus, the transition from static position to active pedalling would affect joint angles [6], and particularly foot positioning [15]- [22]. Authors reported that these alterations would be required in dynamics to maintain a KA allowing for an effective pedalling [6]- [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations